Sequenciamento e análise filogenética de amostras de Zika virus no Brasil - Chanes, Carolina Rodrigues (2018)
Zika virus is an emergent flavivirus transmitted by mosquitos of Aedes genus, was first isolated in 1947 from Zika forest in Africa of the sentinel’s monkeys. The virus spread to other continents and was related with congenital and neurological syndromes in South America and became a public health issue. The genomic sequencing arouses as a crucial tool to obtain answers in real time about infections diseases outbreaks and has helped to understand the origin, phylogeny and trace Zika virus propagation. The main goals of this work are to obtain the complete Zika virus genome sequences that circulated in three different states of Brazil, DF, MT and TO, using the amplification technic multiplex PCR, the MinION portable platform of Oxford Nanopore. Besides that, we had the goal to generate the phylogenetic tree by maximum likelihood to better understand the origin, propagation and dissemination of the virus in these states, and consequentially, in Brazil. The sequences obtain in this present work shown high coverage, 94% to 100% was the coverage of the completeness of the genomes, that presented four distinct lineages, two different clades and related with Northeast samples of Brazil. Finally, our study provides new complete genome sequences of Zika virus in the state of Mato Grosso, demonstrate the relationship of the genome sequences of MT with sequences of Northeast of Brazil and suggests two possible entrances of Zika virus in the state of MT.